Considerations on the H2 desorption process for a combination reactor based on metal and complex hydrides. (15th June 2015) - Bürger, I.; Bhouri, M.; Linder, M.
Abstract: Hydrogen storage systems based on the combination reactor concept are promising for application of future complex hydride materials with high storage capacities and low reaction kinetics at moderate operating temperatures. In such reactors, a fast reacting metal hydride is added to a complex hydride material in a separate compartment of the tank combining the advantages of the high storage capacity of the complex hydride with the high reaction rate of the metal hydride. In the present publication, three issues regarding the desorption performance of such a reactor are discussed based on analytical considerations and 1D simulations. First, it is studied whether the optimal reactor design based on a tubular geometry that has been previously determined for the absorption reaction also enables satisfying desorption performances. It can be concluded from the corresponding simulations that based on the properties of the present reference materials LaNi4.3 Al0.4 Mn0.7 and 2 LiNH2 –1.1 MgH2 –0.1LiBH4 –3 wt.% ZrCoH3, the hydrogen desorption performance of the materials in this reaction geometry is good. Second, it is shown that besides the geometry of the reactor, also its module size is important, as it can be crucial for the thermal management during the desorption. A methodology was developed that allows to analytically determine a first estimate for the best minimum module size configuration – only based on the desorption rate of the basic material. This approach is confirmed by time dependent 1D simulations applying a validated model for the reference materials. Third, the influence of a realistic periodic desorption load on the performance of a combination reactor is studied. The results clearly show that since the addition of a MeH material enables much smaller module sizes, it is advantageous for the thermal management of complex hydride based reactors and increases their flexibility. Highlights: Optimal geometry for desorption process in combination reactor. Effect of module size on desorption performance of a metal hydride reactor. Desorption at varying loads in combination reactor – reabsorption of hydrogen.